A novel method for qualitative analysis of edible oil oxidation using an electronic nose. (1st July 2016) - Xu, Lirong; Yu, Xiuzhu; Liu, Lei; Zhang, Rui
Highlights: A method for qualitative analysis of edible oil oxidation using an E-nose was developed. This rapid and non-invasive method is simpler than classical methods. The sensitivity of this method is excellent for quality control of edible oils. Abstract: An electronic nose (E-nose) was used for rapid assessment of the degree of oxidation in edible oils. Peroxide and acid values of edible oil samples were analyzed using data obtained by the American Oil Chemists' Society (AOCS) Official Method for reference. Qualitative discrimination between non-oxidized and oxidized oils was conducted using the E-nose technique developed in combination with cluster analysis (CA), principal component analysis (PCA), and linear discriminant analysis (LDA). The results from CA, PCA and LDA indicated that the E-nose technique could be used for differentiation of non-oxidized and oxidized oils. LDA produced slightly better results than CA and PCA. The proposed approach can be used as an alternative to AOCS Official Method as an innovative tool for rapid detection of edible oil oxidation.